PENGEMBANGAN MODEL PENDIDIKAN MULTIKULTURAL - Ayi Teiri Nurtiani; Elvinar (Department of Early Childhood Education, STKIP Bina Bangsa Getsempena, 2018)
Multicultural education should be given to the community in order to create harmonization of differences in culture and the establishment of tolerance for diversity, the events of the Jakarta pilkada which in the past have somewhat hurt the sense of diversity in Indonesia. It is inappropriate for political figures to criticize understanding which is not the territory of its power, so as to cause multiple interpretations of its arguments in society. The difference between the characters' culture is a problem that has surfaced so that it becomes difficult to stop public consumption from spreading to all corners of Indonesia, the issue of SARA tends to be unavoidable. For months, Jakarta's political temperature had heated up with prolonged demonstrations which had a domino effect on all parts of Indonesia which caused sentimental differences in culture to be felt. For the sake of anticipating the same event to recur and a prolonged impact, public awareness is needed in understanding multicultural education, that is society that is able to respect each other and respect cultural differences becomes a necessity that needs to be achieved, making the difference into unity values ​​in building this beloved country. Based on the existing phenomena, the research team was interested and desirous to develop a multicultural education model for PG-PAUD STKIP BBG students who are part of the Indonesian community, no longer the condition of students coming from various parts of Aceh who have cultural diversity with each other. It is expected that they will have an awareness of multicultural education so that they can apply it to themselves and teach it to their students later. Abstrak Seyogyanya pendidikan multikultural diberikan kepada masyarakat demi terciptanya harmonisasi atas perbedaan kultur dan terjalinnya toleransi keberagaman, peristiwa pilkada Jakarta yang lalu sedikit banyak telah mencederai rasa keberagaman di Indonesia. Tak sepatutnya tokoh politik mengkritisi pemahaman yang bukan wilayah kuasanya, sehingga menimbulkan multitafsir atas argumentasinya di dalam masyarakat. Perbedaan kultur tokoh tersebut menjadi permasalahan yang mengemuka sehingga menjadi konsumsi publik yang sulit terbendung hingga menjalar ke seluruh pelosok Indonesia, isu SARA cenderung tak terhindarkan. Selama berbulan-bulan, suhu politik Jakarta memanas dengan demonstrasi berkepanjangan yang menimbulkan efek domino ke semua wilayah Indonesia yang menyebabkan sentimentil perbedaan kultul terasa. Demi mengantisipasi peristiwa sama terulang dan dampak berkepanjangan, maka diperlukan kesadaran masyarakat dalam memahami pendidikan multikultural, yakni masyarakat yang mampu saling menghargai dan menghormati perbedaan kultur menjadi sebuah keniscayaan yang perlu diraih, membuat perbedaan menjadi nilai-nilai persatuan dalam membangun negeri tercinta ini. Berdasarkan fenomena yang ada, maka tim peneliti tertarik dan berkeinginan untuk mengembangkan model pendidikan multikultural untuk mahasiswa Prodi PG-PAUD STKIP BBG yang merupakan bagian dari masyarakat Indonesia, apatah lagi kondisi mahasiswa yang datang dari berbagai pelosok daerah Aceh yang memiliki keberagaman kultur satu sama lain. Diharapkan mereka memiliki kesadaran akan pendidikan multikultural sehingga mampu menerapkannya pada diri mereka sendiri dan mengajarkannya kepada anak-anak didik mereka kelak. Kata Kunci: pendidikan multicultural